Twenty-first Century Dental Practice and the Treatment of Nonmicrobial Genetic-based Dental Diseases - Edward F Rossomando (Wolters Kluwer Medknow Publications, 2021)
After W.D. Miller proved a causal relationship between microbes and dental caries and periodontitis, the repair and replacement of damaged or lost teeth resulting from microbial activity dominated 20th century dental practice. In this study, I predict that in the 21st century dental practice will shift to the treatment of those dental diseases not caused by microbes. As dentists already treat some nonmicrobial diseases, I will focus on craniofacial malformations, the group of nonmicrobial diseases usually called birth defects. Some examples include dental dysplasias, cleft lip and palate, and malocclusion. In this study, I introduce the word "dysmorphogenesis" (to replace the term birth defect) as it more appropriately ascribes this subset of nonmicrobial diseases results to mistakes during the formation of craniofacial structures. As dysmorphogenic diseases occur during gestation, their diagnosis and especially their treatment require intervention during embryogenesis. Fortunately, decades of research have shown that mutations are involved in malformations during amelogenesis, palatogenesis, and odontogenesis. Knowledge of which genes are involved, together with recent breakthroughs in Crispr gene editing, make interventions during gestation possible. Those dentists performing gene editing procedures I have previously called Biodontists, because creating the Biodontics specialty will take time. The dental profession including dental educators, dental practitioners, and dental manufacturers should begin discussions now on how best to proceed.